E-Vivasaya: An Efficient Farm Land Data Collection for Transparent Agri-Subsidies Distribution and Prediction of Agricultural Product Demand - M. Prasannakumar, Dr. K.Latha (International Journal of Advanced Science and Technology, 2020)
Improvements in Information and Communication Technology (ICT) and the government initiatives in e-governance are only promoting e-agriculture in India. This process not only improves the condition of Indian agriculture but also the life and working conditions of the farmers. Agriculture subsidies are one of evolving issue in the world. In India from last several years government offers subsidies to agriculture zone in direct & indirect method. But how much they are favorable to agriculture division is query. Though the agricultural divisions really benefited by the subsidies but due to misconduct in distribution methods in providing subsidies and schemes are not reached properly to our farmers. And also inadequate estimation of demand and the consequences of over production or under production can cause serious financial consequences for a seed company. It creates the huge price variation in vegetables and food. To solve these problem this paper proposes a system E-vivasaya was invoked to get the proper records of the farmers and farm lands from the farmers via Mobile App.  The primary objective of this work to classify the farm records (attributes such as soil type, seeding date, cultivated area, crops) and predict the agriculture product demand using Machine learning techniques.